Diurnal changes of remote sensing reflectance over Chesapeake Bay: Observations from the Airborne Compact Atmospheric Mapper. (5th January 2018) - Zhang, Minwei; Hu, Chuanmin; Cannizzaro, Jennifer; Kowalewski, Matthew G.; Janz, Scott J.
Abstract: Using hyperspectral data collected by the Airborne Compact Atmospheric Mapper (ACAM) and a shipborne radiometer in Chesapeake Bay in July–August 2011, this study investigates diurnal changes of surface remote sensing reflectance ( R rs ). Atmospheric correction of ACAM data is performed using the traditional "black pixel" approach through radiative transfer based look-up-tables (LUTs) with non-zero R rs in the near-infrared (NIR) accounted for by iterations. The ACAM-derived R rs was firstly evaluated through comparison with R rs derived from the Moderate Resolution Imaging Spectroradiometer satellite measurements, and then validated against in situ R rs using a time window of ±1 h or ±3 h. Results suggest that the uncertainties in ACAM-derived R rs are generally comparable to those from MODIS satellite measurements over coastal waters, and therefore may be used to assess whether R rs diurnal changes observed by ACAM are realistic (i.e., with changes > 2 × uncertainties). Diurnal changes observed by repeated ACAM measurements reaches up to 66.8% depending on wavelength and location and are consistent with those from the repeated in situ R rs measurements. These findings suggest that once airborne data are processed using proper algorithms and validated using in situ data, they are suitable for assessing diurnal changes in moderately turbid estuaries such as Chesapeake Bay. The findings also support future geostationary satellite missions that are particularly useful to assess short-term changes. Graphical abstract: Highlights: The detectability of Rrs diurnal changes is for the first time investigated. An atmospheric correction algorithm is implemented for retrieving Rrs from ACAM. Uncertainties in ACAM retrieved Rrs is comparable to those from MODIS. The findings could support future geostationary satellite missions.